Clinical perspectives on delivering a Positive Behaviour Support intervention for challenging behaviours following acquired brain injury. Issue 2 (7th February 2023) - Analytis, Penelope; Hicks, Amelia J.; Gould, Kate Rachel; Feeney, Timothy J.; Ponsford, Jennie
ABSTRACT: Challenging behaviours are distressing sequelae for people with acquired brain injury (ABI) and their families. Positive Behaviour Support (PBS) is a collaborative approach focussing on improving quality of life for individuals with ABI presenting with challenging behaviours. This qualitative study explored clinicians' experiences of a 12-month intervention (PBS+PLUS) for adults with ABI and their family/carers. Semi-structured interviews were conducted with eight clinicians trained in neuropsychology ( n  = 5), occupational therapy ( n  = 3), speech pathology ( n  = 2), with two clinicians trained in two of these disciplines. Interviews were analysed through reflexive thematic analysis. Three themes were identified: Shifting clinical identity; Working as equals; Adapting to the environment. Participants experienced PBS+PLUS as a difficult approach to learn but one which enhanced overt client communication and comfort with their clinical fallibility. PBS+PLUS involved giving clients equal status in the clinician–client relationship which for some clients and families was challenging. Finally, PBS+PLUS was perceived as problematic to implement in some work settings (e.g., involving high staff turnover). Clinicians' recommendations for future implementation included thorough training and supervision and early setting of client expectations. With increasing interest in PBS to address challenging behaviours after ABI, these findings will guide PBS+PLUS translation for community clinicians.